2023
DOI: 10.3390/antibiotics12040746
|View full text |Cite
|
Sign up to set email alerts
|

Cefiderocol Efficacy in a Real-Life Setting: Single-Centre Retrospective Study

Abstract: The current carbapenem-resistant gram-negative bacteria (CR-GN) treatment guidelines lack strong evidence about cefiderocol (CFD) efficacy against CR-GN, especially CRAB. The study’s purpose is to evaluate the effectiveness of CFD in a real-life setting. We made a single-center retrospective study of 41 patients who received CFD in our hospital for several CR-GN infections. Bloodstream infections (BSI) affected 43.9% (18/41) of patients, while CRAB affected 75.6% (31/41) of isolated CR-GN patients. Thirty-days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Indeed, in another study [51], FDC was shown to be associated with a higher rate of clinical success in BSI (75%) compared to respiratory infections (45.8%). Similarly, Palermo et al [57] observed a mortality of 61.5% in VAP compared with 46.7% in BSI due to CRAB.…”
Section: Mortalitymentioning
confidence: 81%
See 3 more Smart Citations
“…Indeed, in another study [51], FDC was shown to be associated with a higher rate of clinical success in BSI (75%) compared to respiratory infections (45.8%). Similarly, Palermo et al [57] observed a mortality of 61.5% in VAP compared with 46.7% in BSI due to CRAB.…”
Section: Mortalitymentioning
confidence: 81%
“…However, in this study, the reported resistance to FDC was 60% of the tested isolates. Mortality ranged widely, from 12.5% to 51% [50][51][52]57,[60][61][62][63][64][65]. Adverse events associated with FDC administration were very infrequent, being described in none to less than 5% of treated subjects.…”
Section: Clinical Studies and Case Series Assessing The Efficacy Of F...mentioning
confidence: 99%
See 2 more Smart Citations
“…At the time of writing this manuscript, consistent real-life experiences of cefiderocol use are increasing but are still limited. 7–10 This study aimed to describe the early experience on cefiderocol postmarketing use at three tertiary care hospitals in Italy, to analyse the predictors of 30 day mortality among patients treated with cefiderocol due to infection with MDR pathogens, and to assess whether the use of cefiderocol-based combinations was associated with different outcomes compared with cefiderocol monotherapy.…”
Section: Introductionmentioning
confidence: 99%